Modeling, substrate docking, and mutational analysis identify residues essential for the function and specificity of a eukaryotic purine-cytosine NCS1 transporter. - Krypotou, Emilia; Kosti, Vasiliki; Amillis, Sotiris; Myrianthopoulos, Vassilios; Mikros, Emmanuel; Diallinas, George (J Biol Chem, 2012)
The recent elucidation of crystal structures of a bacterial member of the NCS1 family, the Mhp1 benzyl-hydantoin permease from Microbacterium liquefaciens, allowed us to construct and validate a three-dimensional model of the Aspergillus nidulans purine-cytosine/H(+) FcyB symporter. The model consists of 12 transmembrane α-helical, segments (TMSs) and cytoplasmic N- and C-tails. A distinct core of 10 TMSs is made of two intertwined inverted repeats (TMS1-5 and TMS6-10) that are followed by two additional TMSs. TMS1, TMS3, TMS6, and TMS8 form an open cavity that is predicted to host the substrate binding site. Based on primary sequence alignment, three-dimensional topology, and substrate docking, we identified five residues as potentially essential for substrate binding in FcyB; Ser-85 (TMS1), Trp-159, Asn-163 (TMS3), Trp-259 (TMS6), and Asn-354 (TMS8). To validate the role of these and other putatively critical residues, we performed a systematic functional analysis of relevant mutants. We show that the proposed substrate binding residues, plus Asn-350, Asn-351, and Pro-353 are irreplaceable for FcyB function. Among these residues, Ser-85, Asn-163, Asn-350, Asn-351, and Asn-354 are critical for determining the substrate binding affinity and/or the specificity of FcyB. Our results suggest that Ser-85, Asn-163, and Asn-354 directly interact with substrates, Trp-159 and Trp-259 stabilize binding through π-π stacking interactions, and Pro-353 affects the local architecture of substrate binding site, whereas Asn-350 and Asn-351 probably affect substrate binding indirectly. Our work is the first systematic approach to address structure-function-specificity relationships in a eukaryotic member of NCS1 family by combining genetic and computational approaches.
Keywords: Adenine; Amino Acid; Amino Acid Motifs; Amino Acid Substitution; Aspergillus nidulans; Conserved Sequence; Cytosine; Fungal Proteins; Guanine; Hydrogen Bonding; Hypoxanthine; Kinetics; Molecular Docking Simulation; Molecular Dynamics Simulation; Mutagenesis; Phenotype; Protein; Protein Binding; Protein Structure; Sequence Homology; Site-Directed; Structural Homology; Substrate Specificity; Symporters; Tertiary